Implementation of IoT in Water Quality Monitoring and Management System for Koi Fish Ponds Based on Web with RESTful API - Ida Bagus Gede Baskara; Made Adi Paramartha Putra; Putu Trisna Hady Permana S; I Nyoman Yudi Anggara Wijaya; I Gede Juliana Eka Putra (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Technological advancements, particularly in microcontrollers and the Internet of Things (IoT), have brought significant changes to various aspects of life. Microcontrollers such as the ESP32, DS18B20 sensor, water pH sensor, and other supporting sensors enable the development of efficient automation systems. This research addresses issues related to the design and development of IoT devices for water quality monitoring, as well as the integration of these devices with web-based systems. The objective is to develop a device capable of monitoring water quality parameters such as pH, temperature, turbidity, dissolved materials, salinity projection, and dissolved oxygen projection, while providing automatic notifications under certain conditions. The development process applies the Agile methodology, which allows for rapid and adaptive iterations. Theoretically, this study contributes to improving understanding of IoT implementation and information systems, while practically, it provides a technological solution to support Koi fish farmers in monitoring and managing pond water quality. The expected outcome is a web-based water quality monitoring and management device for Koi ponds that can deliver real-time information and condition notifications, thereby reducing aquaculture risks and improving productivity.